(untitled) (One Health & Risk Management, 2021)
Introduction. Climate change threatens not only the nature and agriculture but also the human health. Education is the key element of the global response to climate change. There is an increasing emphasis on the inclusion of climate change issues in medical education. A medical education curriculum on climate change has the greatest potential to reach large cohorts of professionals and allow for standardization between institutions. In June 2020, New Jersey became the first state in the world which included climate change education in its Student Training Standards. To date, only a few medical schools have changed programs to focus on climate change: the University of Minnesota included climate topics into the training programs for physicians, nurses, and pharmacists; similar changes have been implemented at the Mayo Clinic; at the University of Illinois, first-year students are being trained to predict the asthma flare-ups due to more frequent fires at Microbiology discipline, as well as Lyme disease and other vector-borne microbial diseases. The aim of the current research is to identify directions for developing the medical education curriculum that will help future doctors and physicians to understand the interrelationship between public health and climate change. Material and methods. The main challenges regarding climate change impact, which might interfere with the medical training, can be as follows: new subjects are difficult to incurporate into existing courses, and teachers do not have sufficient knowledge of the subject. The curriculum for medical students provides an optional course training lasting for 50 hours, of which 30 hours will be completed through direct contact and 20 hours by individual work, and includes 11 issue-related introductory topics. A 36-hour curriculum has been initiated for resident-doctors, focusing on the study of the healthy population impacted by climate changes in order to provide appropriate preventive, as well as develop a proper behaviour in case of extreme situations. The curriculum developed for physicians is aimed at strengthening the knowledge of health professionals about the causes, consequences, health impact, ways to reduce and adapt to climate change; it will enable public health institutions to prepare human resources to manage climate change situations that will respond by implementing specific preventive and control measures. The curriculum is designed for 90 hours, divided into 14 topics. Results. In the health training process the problems influenced by climate change can be: new subjects are difficult to include in existing courses, teachers do not have enough knowledge about the subject. The curriculum for students provides an optional course training with a duration of 50 hours of which 30 hours will be completed through direct contact and 20 hours for individual work and includes 11 introductory topics in the problem. A 36-hour curriculum is initiated for resident-doctors with an emphasis on studying the impact on the healthy population in order to organize prophylactic measures of the consequences of climate change but also the correct conduct in extreme situations. The curriculum developed for physicians is aimed at strengthening the knowledge of health professionals about the causes, consequences, health impact, ways to reduce and adapt to climate change; will allow public health institutions to have human resources trained in the management of situations influenced by climate change, which will respond by implementing prevention and control measures in the field. This curriculum provides a duration of 90 hours divided into 14 topics. Conclusions. The implementation of training on climate change is an indisputable topic, so, the curriculum development might be the first step in initiating the instructional process.